A moving context-aware and location-based paratransit system. (2015) - Dow, Chyi-Ren; Lai, Po-Yu; Ye, Jhen-He
In recent years, paratransit services have been a crucial development for serving people with disabilities. However, the operators face difficulties in efficiently monitoring a paratransit vehicle and passengers are difficult to know the arrival status of the vehicle. This study proposes a moving context-aware and location-based paratransit system. With the support of WAVE/DSRC vehicular communication systems and internet access, our system can integrate the paratransit operator centre, paratransit vehicle and passenger to provide real-time services. Moving context analysis is performed to evaluate the impact of gender, device size and the ways to hold the device and the results are integrated into the development of our prototype system. Visual and audio notification services can be provided adaptively to a passenger based on the behaviour state of the passenger and the location of the paratransit.